Chemical composition and antioxidant activity of sulphated polysaccharides extracted from Fucus vesiculosus using different hydrothermal processes - Rodríguez-Jasso, Rosa María (2014)
Sulphated polysaccharides (SP) were extracted from Fucus vesiculosus seaweed by using two different hydrothermal processes: microwave-assisted extraction (MAE) and autohydrolysis (AH). The extraction yields, chemical composition, and antioxidant activity of the polysaccharides extracted were determined and compared. Although both processes afforded SP with similar yields (18.2 mass % and 16.5 mass %, for MAE and AH, respectively) and l-fucose as the main monosaccharide, the heterogeneous structure of the polysaccharide recovered was significantly affected by the AH process. The SP obtained by MAE contained 53.8 mole % of fucose, 35.3 mole % of xylose, and 10.8 mole % of galactose; while the SP obtained by AH was composed of 76.8 mole % of fucose and 23.2 mole % of galactose. Both samples presented comparable values of antioxidant activity by the di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium (2,2-diphenyl-1-picrylhydrazyl, DPPH), 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS), and lipid oxidation inhibition methods, but the polysaccharide obtained by AH exhibited a higher antioxidant potential by the differential pulse voltammetry technique. This study demonstrates that the chemical composition and antioxidant activity of SP obtained from F. vesiculosus vary according to the process used for their extraction. However, the SP obtained by MAE or AH both have the potential for use as natural antioxidants in industrial applications.